(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
In this article I analyze the explicit use of the label conspiracy theory in political communication from the argumentative point of view. I am not interested here in the content of any specific conspiracy theory, but in the kind of argumentative force the label has when used by a political speaker to refer to opponents. The examples discussed are public statements by two contemporary center-left American leaders. To show the kind of argumentative force that the label conspiracy theory conveys when used in political discourse, I reconstruct the speakers’ arguments using Walton diagrams. I also apply Tindale’s rhetorical notion of making present and Govier’s ideas about logical and social oppositions to advance the idea that a social dynamic based on a radical dichotomy is at play as soon as the label conspiracy theory is mentioned.